Local Government Expansion of Mobile Governance during the Pandemic - Binti Azizatun Nafi'ah (Jurnal Borneo Administrator, 2023)
During the COVID-19 pandemic, mobile governance has been more popular than old public services since the government implemented social distancing and stay at-home policies. This study will contribute to the scientific literature on m-governance and public administration application development in Indonesia. This study aims to examine local government applications and identify application categories owned by local governments in East Java Province. This study uses a quantitative approach and secondary data from the Android smartphone Play Store. After data collection, the researcher applied descriptive statistical analysis to quantify applications made by the local government in East Java Province. Finally, the researcher classified those applications into enterprise- and citizen focused apps. The results found that local governments in East Java Province have 362 m-governance applications. The regional offices in East Java used at least 15 uniform applications. Most applications (86%) focused on community service; the rest were business-oriented. The highest category was productivity communication applications and 14% of applications focused on business activities. Thus, based on the topic, this study is the first to examine how local governments might categorize Android-based applications.